Non-linear magnetohydrodynamic simulations of pellet triggered edge-localized modes in JET. (18th December 2019) - Futatani, S.; Pamela, S.; Garzotti, L.; Huijsmans, G.T.A.; Hoelzl, M.; Frigione, D.; Lennholm, M.
Abstract: Non-linear magnetohydrodynamic simulations of pellet-triggered edge-localized modes (ELMs) in JET plasma have been carried out with the JOREK code. The pellet particle fuelling efficiency and the power flux at the divertor target during the pellet-triggered ELM have been studied. The pellet injection in unstable plasma delivers the particle fuelling but the pellet fuelling rate is smaller than the rate of particle loss during the pellet triggered ELM. The JOREK simulations estimate the power flux at the divertor target and found good agreement with the experimental observation. The energy deposition of the pellet triggered ELM shows a toroidally asymmetric profile. However, and due to this toroidal asymmetry, this effect cannot be captured by the existing layout of the divertor infra-red (IR) cameras available in JET. This work highlights the benefit of having a larger number of IR cameras to analyse the heat flux for the experiments which are assumed to be toroidally asymmetric, such as the pellet and/or gas injection experiments.